1987
DOI: 10.1128/aac.31.12.1935
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity against reference strains and field isolates of Treponema hyodysenteriae

Abstract: The in vitro susceptibilities of eight isolates of Treponema hyodysenteriae from pigs naturally infected with swine dysentery between 1976 and 1983 were determined by an agar dilution technique. Carbadox, olaquindox, tiamulin, metronidazole, furazolidone, and monensin were the most active against these field isolates regardless of the year of recovery. The influence of inoculum size on the MICs against four reference strains of T. hyodysenteriae was studied. Various degrees of activities of ampicillin and linc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
18
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
7
18
0
Order By: Relevance
“…When compared with the MIC 90 of S. hyodysenteriae strains against tiamulin, the North American isolates of S. pilosicoli were similar. 2,15,16,20,21,29,30,38 Thus, as previously shown for S. hyodysenteriae, 8,[15][16][17]20,21,29,30,38 S. pilosicoli is highly sensitive to tiamulin.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…When compared with the MIC 90 of S. hyodysenteriae strains against tiamulin, the North American isolates of S. pilosicoli were similar. 2,15,16,20,21,29,30,38 Thus, as previously shown for S. hyodysenteriae, 8,[15][16][17]20,21,29,30,38 S. pilosicoli is highly sensitive to tiamulin.…”
Section: Discussionsupporting
confidence: 53%
“…2,8,9,[14][15][16][17][20][21][22]29,30,38,39 Because S. pilosicoli was recognized only recently, little information is available about the in vitro antimicrobial susceptibility of this spirochete. 8,9,14,21,29,30 The results of the present in vitro study indicated that 100% of the isolates were susceptible to carbadox and tiamulin, whereas the suceptibility to lincomycin and gentamicin differed among the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The solid medium most commonly used for the antimicrobial susceptibility testing of B. hyodysenteriae is Trypticase soy agar with 5% ox or ssheep blood (8,14,23,26,29). In general, the MIC is reported as the lowest concentration of the antimicrobial agent that prevents growth or hemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial agents most frequently used in Sweden and many other countries for the treatment of the disease are tylosin and tiamulin. Widespread resistance to tylosin, a 16-membered macrolide antibiotic, in B. hyodysenteriae has been reported in several countries (2,14,17,23). This resistance is caused by a point mutation in the 23S rRNA gene (9).…”
mentioning
confidence: 99%
“…To determine susceptibility of B. hyodysenteriae to doxycycline, the ADM was used. In most laboratories, quantitative susceptibility testing of brachyspiras is commonly done by diluting the antibacterial substance in agar media (Kitai et al 1987;Ronne and Szancer 1990;Smith et al 1991;Trott et al 1996;D uhamel et al 1998;Hommez et al 1998;Fossi et al 1999) or by the broth dilution method (Hayashi et al 1988;Buller and Hampson 1994;Karlsson et al 2002). Apart from applying the agar dilution method, which has been used by our laboratory on a daily basis for several years, a semi-quantitative method, namely the Epsilometer test for B. hyodysenteriae susceptibility to doxycycline, was analyzed.…”
Section: Discussionmentioning
confidence: 99%